Comparison of the outcomes for retrograde intrarenal surgery (RIRS) and percutaneous nephrolithotomy (PCNL) in the treatment of renal stones more than 2 centimeters - Nualyong, Chaiyong; Sathidmangkang, Supachai; Woranisarakul, Varat; Taweemonkongsap, Tawatchai; Chotikawanich, Ekkarin (Insight Urology, 2019)
Objective: Comparison of the treatment of large renal stone outcomes between PCNL and RIRS. Material and Method: Retrospective study of patients with large renal calculi who underwent stone treatment at Siriraj Hospital between July 2012 and September 2016. Patients were reviewed and divided into group I (PCNL, n=73) and group II (RIRS, n=67). The outcomes, including operating time, length of hospital stay, complications, stone-free rates and retreatment rates, were collected and compared. Result: Stone-free rates were 79.4% in group I and 74.6% in group II (p=0.497). Retreatment rates were 53.3% in group I and 47% in group II (p=0.723), while operative time (p=0.001), length of hospital stays (p<0.001), and complications (p<0.001) were statistically different. Main stone compositions were calcium oxalate monohydrate (38%) and calcium phosphate (23%). Conclusion: Treatment of kidney stones 2-4 centimeters in size with PCNL or RIRS was comparable with satisfactory outcomes.